MCATs: Case report of adnexal adenocarcinoma of not otherwise specified type - Tetyana Svyatenko; Andrii Prokhach; Stepan Antoniuk; Vadym Hurtovyy; Denys Tereshkov; Anna Prokhach (Clinical Case Reports)
Malignant cutaneous adnexal tumors are rare dermatosis that can have extradermal twins. Diagnosis of adnexal skin tumors is sometimes difficult. Immunohistochemistry has limited value in the diagnosis. Most adnexal skin tumors are localized on the head and neck. Difficulties in their diagnosis associated with absence of strict clinical criteria.